2005
DOI: 10.1097/01.rli.0000167425.34577.d1
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Predictive Value of Electrical Impedance Scanning in BI-RADS Category IV Breast Lesions

Abstract: With a NPV of 97.1% of EIS in BI-RADS category IV breast lesions, a negative result in these lesions could be firm indication to manage them as BI-RADS-category III and refer patients for a 6-month short-interval follow-up rather than performing a biopsy. The best adjunctive diagnostic performance can be achieved by a combination of US and EIS. Costs and patient morbidity could be minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Inclusion of women age 40-45 undergoing annual screening mammography also permitted an assessment of sensitivity in non-palpable lesions since at the age range of 30-39 years women with non-palpable findings are rarely biopsied. In fact, T-Scan sensitivity was increased in smaller lesions, which is consistent with previously published reports [17][18][19][20]. Not only are EIS characteristics independent of patient age in the pre-menopausal breast, but also importantly, T-Scan specificity and sensitivity in this study were found to be independent of breast lesion palpability.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Inclusion of women age 40-45 undergoing annual screening mammography also permitted an assessment of sensitivity in non-palpable lesions since at the age range of 30-39 years women with non-palpable findings are rarely biopsied. In fact, T-Scan sensitivity was increased in smaller lesions, which is consistent with previously published reports [17][18][19][20]. Not only are EIS characteristics independent of patient age in the pre-menopausal breast, but also importantly, T-Scan specificity and sensitivity in this study were found to be independent of breast lesion palpability.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, even for the lower bound of the 95% confidence interval of the estimated sensitivity (17.4%), the relative probability significantly exceeded the study success criterion of 2.0 (Pr ¼ 3.27). In fact, T-Scan sensitivity was increased in smaller lesions, consistent with previously published reports [17,18,20]. Importantly, T-Scan specificity and sensitivity were found to be independent of breast lesion palpability on CBE.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite wide-ranging experimental work and technological development, only recently have high-speed software processing platforms made possible clinically useful EIS cancer detection systems. A significant body of data published recently supports the potential for differences in the bioelectrical signature of malignant and benign/normal tissues to be used in cancer detection including melanoma, malignant lymph nodes, thyroid and breast cancer [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…6,[16][17][18]23,24,27,28,30 At present, the EIS system applied in clinical practice is TransScan TS 2000, which was approved by the U.S. FDA for diagnostic use on breast lesions in 1999. It was later developed into the T-Scan 2000ED.…”
Section: Introductionmentioning
confidence: 99%